A case of SLE with pancreatitis - Jain, Karan; Palange, Amit A.; Gokhale, Vijayashree S.; Kakrani, Arjun Lal (International Journal of Research in Medical Sciences, 2017)
Systemic lupus erythematosus (SLE) is a chronic, autoimmune inflammatory disease characterized by the presence of autoantibodies, immune complex formation, and multiple organ system involvement. Gastrointestinal manifestations are common in SLE patients, but acute pancreatitis is rare. Here we present a case of a 23 yrs. old male who came to the medicine OPD with the chief complaints of pain in abdomen, swelling all over the body since, 8 days and multiple joint pain for 1 and half months. On examination he was febrile pallor present with anasarca, periorbital edema with heliotrope around both eyes. Dry and xerotic ski over the face, butterfly rash present. Blood investigations, USG and CECT suggestive of acute panceatitis. Patient was treated in ICU for pancreatitis. Patient was found to be hypothyroid and treated with thyroid supplements. ANA BLOT was suggestive of SLE. Renal biopsy showed diffuse proliferative lupus nephritis. Hence our patient had pancreatitis possibly due to SLE induced hypertriglyceridemia.